PSYCHOLOGICAL IMMUNITY AND ITS RELATIONSHIP TO FUTURE ANXIETY AMONG STUDENTS OF THE FOURTH STAGE OF THE DEPARTMENT OF PHYSICAL EDUCATION AND SPORTS SCIENCES - Assist. Prof. Dr. Sukaina Shaker Hassan (Galaxy International Interdisciplinary Research Journal, 2023)
The research aims to identify the level of psychological immunity and future anxiety among the research sample, in addition to identifying the relationship between psychological immunity and independent anxiety among the research sample. As for the research hypothesis, it represented the existence of a significant correlation between psychological immunity and future anxiety among the research sample. The problem of the research was to answer the following question: What is the level of psychological immunity and future anxiety possessed by the students of the fourth stage of the Department of Physical Education and Sports Sciences? And the extent of the impact of future anxiety on the level of psychological immunity among students? As for the research sample, students of the fourth stage, Department of Physical Education and Sports Sciences / College of Basic Education / Al-Mustansiriya University for the academic year 2022-2023, whose number is (31) students, as questionnaires were distributed to them and statistical methods were extracted. The researcher reached a set of results, including that the students were distinguished by a good level of psychological immunity compared to future anxiety, and that the greater the psychological immunity, the less future anxiety among students. The researcher recommended conducting studies similar to the current study by comparing the stages and working on conducting studies related to psychological immunity and paying more attention to the psychological and counseling aspects.